Relationship between Job Burnout and Quality of Life in Healthcare Workers: Preliminary Results of the Health Cohort of Staff in Shahid Beheshti University of Medical Sciences - Sahar Sotoodeh Ghorbani; Hamid Soori (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Job burnout is one of the major reasons for frequent job changes that creates physical and mental problems and reduces efficiency and at workplace. This study aimed to investigate the relationship between the quality of working life and job burnout in a large sample of health workers. Materials and methods: The present study was part of the first stage of Health Cohort of Staff in Shahid Beheshti University of Medical Sciences, performed in 1274 participants. The WHOQOL-BREF and the Maslach Job Burnout Inventory (1985) were administered. Data were analyzed using STATA applying Shapiro Wilk, Spearman correlation coefficient, and Linear Regression Analysis. Results: There was a significant inverse relationship between the quality of working life and job burnout (r = -0.234, P= 0.001). Among the dimensions of quality of life, only t corresponding to the beta of physical health (r= -0.260) was found to be significant at the error level of less than 5% (P=0.026). Significant inverse relationship were seen between quality of life, emotional fatigue, and depersonalization (r= -0.117, P= 0.001 and r= -0.080, P= 0.004, respectively) and a significant direct relationship was observed between quality of life and individual performance (r= 0.116, P= 0.001). Conclusion: According to the inverse relationship between job burnout and quality of life, authorities should aim at identifying the factors associated with lower quality of working life, and especially improve physical health to prevent job burnout and ultimately increase productivity.